The Inner Exiles. Outlaws and Scapegoating Process in Grettis saga Ásmundarsonar and Gísla saga Súrssonar - Poilvez, Marion, 1986- (2011)
Was Icelandic outlawry exceptional? The legal and historical aspect of Icelandic outlawry has been widely studied and commented by scholars (Spoelstra, 1938), either by following indications from the Grágás or through the use of literary examples spread in the sagas (Frederic Amory, 1992). As main characters of a narrative, Grettir and Gísli were allusively compared through the theme of home and homelessness in medieval Iceland (Miller, 2004), or connected with other tales about outlaws from Europe gathered in the so-called «Matter of Greenwood» (Maurice Keen, 1987), or even supposed to belong to a large Anglo-Norse common tradition on outlaws (Joost De Lange, 1935). However, the two stories have been so far mainly discussed in connection with other tales on outlaws from Europe, but surprisingly not very often together. Grounded on historical, literary and anthropological views, this thesis will attempt to relocate the two sagas in their specific Icelandic context and underline the specific nature of the Icelandic full outlawry as well as its consequences in the narrative. While being banned from the community in continental Europe allowed a man to start a new life in another place, Icelandic outlaws were excluded from the social space of the island, yet kept inside (oferjanði). Why keep trouble-makers inside the enclosed space of the island instead of forcing them to leave the place definitely, as it was the case with sentences to lesser outlawry? The fact to be stuck on the island but out of the public scene leads to the creation of new original and individualized narrative spaces: the haunted wilderness for Grettir, the haunted dreams for Gísli. Through the analysis of the concepts of exile and liminality, this study defines the space the outlaw is forced to occupy (out and under) and teases out the picture of an “inner-exile”, both cause and consequence of outlawry. This inner exile is revealed through a contrastive narrative process, a common structure in the two sagas. From this analysis, the theory of the ...